KARAKTERISTIK PERSALINAN PREMATUR DI RSUP PROF. DR. R. D. KANDOU MANADO - Oroh, Siva; Suparman, Eddy; Tendean, Hermie M. M. (e-CliniC, 2015)
Abstract: Preterm labor is labor that occurs at 20 - <37 weeks gestational age calculated from the first day of the last menstrual period. Preterm labor is one cause of neonatal morbidity and mortality, which is 60-80% worldwide. This was a retrospective and descriptive study using the medical record of the Department of Obstetrics & Gynecology/Prof. Dr. R.D. Kandou General Hospital Manado period of January 1st to December 31st 2013. There were 151 premature labors during that period. The most frequent characteristics were age group 21-34 years, high school education, and house wife. Based on the parity status, the highest number was P0. History of abortion was found only in a small part of samples. The highest number of diseases/complications was rupture of membrane. The most frequent type of labor was spontaneous labor with back of the head position.Keywords: premature birth, premature babyAbstrak: Persalinan prematur adalah persalinan yang berlangsung pada usia kehamilan 20 - <37 minggu dihitung dari hari pertama haid terakhir. Persalinan prematur merupakan salah satu penyebab utama morbiditas dan mortalitas neonatal, yaitu 60-80% di seluruh dunia. Penelitian ini bersifat deskriptif retrospektif dengan memanfaatkan data sekunder berupa catatan medik di Bagian Obstetri Ginekologi/BLU RSUP Prof. Dr. R. D. Kandou Manado periode 1 Januari-31 Desember 2013. Hasil penelitian mendapatkan 151 sampel kasus persalinan prematur. Karakteristik berdasarkan usia ibu terbanyak pada usia 21-34 tahun, pendidikan ibu terbanyak SMA, dan pekerjaan IRT. Berdasarkan paritas didapatkan jumlah tertinggi pada P0, riwayat abortus hanya sebagian kecil ibu, penyakit/penyulit tersering ialah ketuban pecah dini, dan jenis persalinan tersering ialah spontan letak belakang kepala.Kata kunci: persalinan prematur, bayi prematur